2008
DOI: 10.1007/s10290-008-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

The U-Shaped Productivity Dynamics of French Exporters

Abstract: Sunk costs due to entry into foreign markets are used as the main justification of the relationship between firm productivity and exports. We use a large-scale dataset on French manufacturing firms to evaluate how sunk costs affect the productivity of new exporters. We find that the typical productivity dynamics of a new exporter is U-shaped. Prior to entry into export markets, firm productivity temporarily decreases. It recovers contemporaneously with entry, as the benefits from sales to foreign markets are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
3
19
2
Order By: Relevance
“…with the theoretical literature (Melitz, 2003), this results is consistent with Bellone et al (2008b), where a U-shaped productivity pattern is revealed for future French exporters. 19…”
Section: Accounting For Time Duration To Export Marketssupporting
confidence: 81%
See 1 more Smart Citation
“…with the theoretical literature (Melitz, 2003), this results is consistent with Bellone et al (2008b), where a U-shaped productivity pattern is revealed for future French exporters. 19…”
Section: Accounting For Time Duration To Export Marketssupporting
confidence: 81%
“…This assumption is supported by an expanding empirical literature (see, among others, Bernard and Wagner, 2001;Das et al, 2001;Tybout, 2001;Bellone et al, 2008b).…”
Section: Introductionsupporting
confidence: 56%
“…Bellone et al (2008) find that over the 1990-2002 period, 73% of French firms with at least 20 employees engaged in export. The percentage of Italian manufacturing firms involved in export activities is in line with that in other European countries.…”
Section: Institutional Backgroundmentioning
confidence: 97%
“…The figure of 68.5% is also in the range of what is found by other studies for European countries. Using data from the French Manufacturing Census over the period 1990, Bellone et al (2007 find that 73% of French firms with at least 20 employees engaged in exports. For Sweden, Hansson and Lundin (2004) obtain that around 89% of manufacturing firms with more than 50 employees exported during the period 1990-1999 (data drawn from a survey conducted by Statistics Sweden).…”
Section: Exportsmentioning
confidence: 99%